At home with surface computing - Kirk, David; Izadi, Shahram; Hilliges, Otmar; Taylor, Stuart; Sellen, Abigail; Banks, Richard (Proceedings of CHI 2012, 2012)
This paper describes a field study of an interactive surface deployed in three family homes. The tabletop technology provides a central place where digital content, such as photos, can be easily archived, managed and viewed. The tabletop affords multi-touch input, allowing digital content to be sorted, triaged and interacted with using one or two-handed interactions. A physics-based simulation adds dynamics to digital content, providing users with rich ways of interacting that borrows from the real-world. The field study is one of the first of a surface computer within a domestic environment. Our goal is to uncover people‘s inter-actions, appropriations, perceptions and experiences with such technologies, exploring the potential barriers to use. Given these devices provide such a revolutionary shift in interaction, will people be able to engage with them in everyday life in the ways we intend? In answering this question, we hope to deepen our understanding of the design of such systems for home and consumer domains.